A Critical Review and Best‐Practice Recommendations for Control Variable Usage. Issue 1 (4th June 2015) - Bernerth, Jeremy B.; Aguinis, Herman
Abstract : The use of control variables plays a central role in organizational research due to practical difficulties associated with the implementation of experimental and quasi‐experimental designs. As such, we conducted an in‐depth review and content analysis of what variables, and why such variables are controlled for, in 10 of the most popular research domains (task performance, organizational citizenship behaviors, turnover, job satisfaction, organizational commitment, employee burnout, personality, leader‒member exchange, organizational justice, and affect) in organizational behavior/human resource management (OB/HRM) and applied psychology. Specifically, we examined 580 articles published from 2003 to 2012 in AMJ, ASQ, JAP, JOM, and PPsych . Results indicate that, across research domains with clearly distinct theoretical bases, the overwhelming majority of the more than 3, 500 controls identified in our review converge around the same simple demographic factors (i.e., gender, age, tenure), very little effort is made to explain why and how controls relate to focal variables of interest, and control variable practices have not changed much over the past decade. To address these results, we offer best‐practice recommendations in the form of a sequence of questions and subsequent steps that can be followed to make decisions on the appropriateness of including a specific control variable within a particular theoretical framework, research domain, and empirical study. Our recommendations can be used by authors as well as journal editors and reviewers to improve the transparency and appropriateness of practices regarding control variable usage.